Must Clinics Replace 2D by 3D Environments for an Efficient Training of Laparoscopic Novices? A Critical Analysis of the Learning Curve for Basic Skills - Sahm, Maik; Danzer, Clara; Grimm, Alexis Leonhard; Herrmann, Christian; Mantke, Rene (Frontiers in Surgery, 2022)
ABSTRACT Background and aims: Published studies repeatedly demonstrate an advantage of three-dimensional (3D) laparoscopic surgery over two-dimensional (2D) systems, but with quite heterogeneous results. This raises the question whether clinics must replace 2D technologies to ensure an effective training of future surgeons. Methods: We recruited 45 students with no experience in laparoscopic surgery and comparable characteristics in terms of vision and frequency of video game usage. The students were randomly allocated to 3D (n=23) or 2D (n=22) groups and performed ten runs of a laparoscopic “peg transfer” task in the Luebeck Toolbox. A repeated-measures ANOVA for operation times and a generalized linear mixed model for error rates were calculated. Main effects of laparoscopic condition and run, as well as the interaction term between the two, were examined. Results: No statistically significant differences in operation times and error rates were observed between 2D and 3D group (p = .10 and p = .72, respectively). The learning curve showed a significant reduction in operation time and error rates (both p’s < 0.001). No significant interactions between group and run were detected (operation time: p = .342, error rates: p = .83). With respect to both endpoints studied, the learning curves reached their plateau at the 7th run. Conclusion: The result of our study with laparoscopic novices revealed no significant difference between 2D and 3D technology with respect to performance time and error rate in a simple standardized test. In future, surgeons may thus still be trained in both techniques.